Anatomy of the Ediacaran rangeomorph Charnia masoni. (11th September 2018) - Dunn, Frances S.; Wilby, Philip R.; Kenchington, Charlotte G.; Grazhdankin, Dmitriy V.; Donoghue, Philip C. J.; Liu, Alexander G.
Abstract: The Ediacaran macrofossil Charnia masoni Ford is perhaps the most iconic member of the Rangeomorpha: a group of seemingly sessile, frondose organisms that dominates late Ediacaran benthic, deep‐marine fossil assemblages. Despite C. masoni exhibiting broad palaeogeographical and stratigraphical ranges, there have been few morphological studies that consider the variation observed among populations of specimens derived from multiple global localities. We present an analysis of C. masoni that evaluates specimens from the UK, Canada and Russia, representing the largest morphological study of this taxon to date. We describe substantial morphological variation within C. masoni and present a new morphological model for this species that has significant implications both for interpretation of rangeomorph architecture, and potentially for existing taxonomic schemes. Previous reconstructions of Charnia include assumptions regarding the presence of structures seen in other rangeomorphs (e.g. an internal stalk) and of homogeneity in higher order branch morphology; observations that are not borne out by our investigations. We describe variation in the morphology of third and fourth order branches, as well as variation in gross structure near the base of the frond. The diagnosis of Charnia masoni is emended to take account of these new features. These findings highlight the need for large‐scale analyses of rangeomorph morphology in order to better understand the biology of this long‐enigmatic group.